Alteration of the content of minor elements in apoptotic cells induced by anti-cancer drugs with synchronous radiation - Chen, Li-Rong; Zheng, Shu; Chen, Yu-Fa; Zhang, Su-Zhan; Huang, Yu-Ying (Zhejiang da xue xue bao. Journal of Zhejiang University. Medical sciences. Yi xue ban, 2002)
OBJECTIVE: To explore the change of content of minor elements and its biological implication in apoptotic processes. METHODS: The content of minor elements of apoptotic cells from breast cancer induced by anti-cancer drugs was quantitatively analysed with synchronous radiation X-ray fluorescence. RESULTS: Seven kinds of minor elements including Ti, Cr, Fe, Cu, Zn, Ga and Ge as well as five major elements P, S, Ca, Cl and K were detected in the apoptotic and control cells. The content of elements Zn and P in apoptotic cells after 48 h treatment with taxol and colchicine was significantly increased higher than that in the control cells P<0.05). The content of element Fe in 48 h treatment with taxol was significantly decreased lower than that in the control cells P<0.05). The same trend of change of elements was observed during the process of apoptotic cells death induced with VP-16 or cycloheximide. CONCLUSION: This results suggest that the elements Zn, Fe and P should be involved in apoptosis induced by anti-c